2004
DOI: 10.1385/mo:21:2:187
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Activities Controlling Adenosine Levels in Normal and Neoplastic Tissues

Abstract: Adenosine is known to be associated with effects such as inhibition of immune response, coronary vasodilation, stimulation of angiogenesis, and inhibition of inflammatory reactions. Some authors suggest that adenosine may also have similar functions in tumor tissues. Tissue levels of adenosine are under close regulation by different enzymes acting at different levels. Adenosine is produced from AMP by the action of 5'-nucleotidase (5'-NT) and is converted back into AMP by adenosine kinase (AK) or into inosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 25 publications
4
22
0
1
Order By: Relevance
“…Our further results demonstrated that AB61 is phosphorylated in HCT116 colon cancer cell line (cytotoxicity IC 50 ¼ 1.9 nmol/L) but the phosphorylation does not proceed in normal BJ fibroblasts (cytotoxicity IC 50 ¼ 8 mmol/L). These data are in accordance with the fact that expression of adenosine kinase, the enzyme that might be involved in the phosphorylation of AB61, is increased in colorectal tumors compared with the normal tissue (33)(34)(35). These findings reveal the importance of intracellular phosphorylation for both the efficiency and cancer selectivity of AB61 and suggests for potentially synergistic combinations with therapies increasing nucleoside phosphorylation rates in tumors, for example, radiation (36).…”
Section: Discussionsupporting
confidence: 85%
“…Our further results demonstrated that AB61 is phosphorylated in HCT116 colon cancer cell line (cytotoxicity IC 50 ¼ 1.9 nmol/L) but the phosphorylation does not proceed in normal BJ fibroblasts (cytotoxicity IC 50 ¼ 8 mmol/L). These data are in accordance with the fact that expression of adenosine kinase, the enzyme that might be involved in the phosphorylation of AB61, is increased in colorectal tumors compared with the normal tissue (33)(34)(35). These findings reveal the importance of intracellular phosphorylation for both the efficiency and cancer selectivity of AB61 and suggests for potentially synergistic combinations with therapies increasing nucleoside phosphorylation rates in tumors, for example, radiation (36).…”
Section: Discussionsupporting
confidence: 85%
“…Several studies investigated the change of the adenosine deaminase activity in various cancerous patients. Many authors have shown the increase of serum tADA activity in these patients (4,7,(23)(24)(25)(26). Adapted to previous data, our results showed higher ADA activity in patients with lung cancer compared to controls.…”
Section: Discussionsupporting
confidence: 84%
“…Biri et al [14] demonstrated that decreased activities of ADA in prostate cancer tissue compared with normal prostate tissue. Vannoni et al [15] found very high activities of ADA in colorectal carcinoma as compared with normal colonic mucosa. Aghaei et al [16] studied total ADA and its isoenzyme (ADA-1 and ADA-2) activities in serum, benign and malignant breast tissues and they showed that ADA activities of patients with breast cancer were significantly higher than benign group and healthy subjects.…”
Section: Discussionmentioning
confidence: 97%
“…High ADA activity in malignant tumors may give selective advantage to the cancer cells via production of hypoxanthine guanine phosphoribosyl transferase (HGPRT). This is a key enzyme for the salvage pathway [15]. In recent years there has been expanding interest in the use of some antigens, hormones, and enzymes for the diagnosis of malign tumors and also for the assessment to the response to treatment.…”
Section: Discussionmentioning
confidence: 99%